Transformation of Teacher Professionalism: A Critical Analysis of the Implementation of the Merdeka Curriculum in Sigi Regency - Nurul Fitriah Aras; Sukri; Sinta Satria Dewi Pendit; Sisriawan Lapasere; Andi Nur Isnayanti (Universitas Pendidikan Ganesha, 2025)
Teachers in rural areas often face obstacles in implementing new curricula due to limited resources and uneven professional readiness. In Sigi Regency, this challenge is particularly evident in the adoption of the Merdeka Curriculum in elementary schools. This study analyzes teachers’ understanding of the Merdeka Curriculum and identifies factors that influence both successes and challenges in its implementation. Using a qualitative case study approach at SDN Lonja, data were gathered from six teachers and one principal through observation, semi-structured interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana interactive model. Findings show that teachers’ understanding is at a moderate level (25%–50%), with varying mastery of basic concepts, integration of the Pancasila Student Profile, implementation of the P5 project, and formative assessment. Key barriers include limited training, weak infrastructure, and reliance on conventional teaching methods. Supportive factors, such as principal leadership, collaboration among teachers, and the Merdeka Mengajar Platform, help facilitate adaptation but cannot fully overcome structural constraints. Overall, implementation is gradual and partial, shaped by local conditions and school readiness. The research implies that effective curriculum implementation requires context-sensitive support, sustained professional development, and stronger teacher collaboration.